Aminated nanomicelles as a designer vaccine adjuvant to trigger inflammasomes and multiple arms of the innate immune response in lymph nodes - Song C (Dove Medical Press, 2017)
Chanyoung Song,1,* Hathaichanok Phuengkham,1,* Sun-Young Kim,1 Min Sang Lee,2 Ji Hoon Jeong,2 Sung Jae Shin,3 Yong Taik Lim1 1SKKU Advanced Institute of Nanotechnology, School of Chemical Engineering, 2Department of Pharmacy, Sungkyunkwan University, Suwon, 3Department of Microbiology and Institute for Immunology and Immunological Diseases, Brain Korea 21 PLUS Project for Medical Science, Yonsei University College of Medicine, Seoul, Republic of Korea *These authors contributed equally to this work Abstract: In this study, we suggest a designer vaccine adjuvant that can mimic the drainage of pathogens into lymph nodes and activate innate immune response in lymph nodes. By the amination of multivalent carboxyl groups in poly-(γ-glutamic acid) (γ-PGA) nanomicelles, the size was reduced for rapid entry into lymphatic vessels, and the immunologically inert nanomicelles were turned into potential activators of inflammasomes. Aminated γ-PGA nanomicelles (aPNMs) induced NLRP3 inflammasome activation and the subsequent release of proinflammatory IL-1β. The NLRP3-dependent inflammasome induction mechanism was confirmed through enzyme (cathepsin B and caspase-1) inhibitors and NLRP3 knockout mice model. After the aPNMs were combined with a clinically evaluated TLR3 agonist, polyinosinic–polycytidylic acid sodium salt (aPNM-IC), they triggered multiple arms of the innate immune response, including the secretion of pro-inflammatory cytokines by both inflammasomes and an inflammasome-independent pathway and the included type I interferons. Keywords: vaccine adjuvant, nanoparticles, innate immunity, antigen-presenting cells, lymphatic vessel, type I interferon